2007
DOI: 10.1038/sj.jcbfm.9600475
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin1/TIE2 and VEGF/FLK1 Induced by MSC Treatment Amplifies Angiogenesis and Vascular Stabilization after Stroke

Abstract: Bone marrow stromal cells (MSCs) increase vascular endothelial growth factor (VEGF) expression and promote angiogenesis after stroke. Angiopoietin-1 (Ang1) and its receptor Tie2 mediate vascular integrity and angiogenesis as does VEGF and its receptors. In this study, we tested whether MSC treatment of stroke increases Ang1/Tie2 expression, and whether Ang1/Tie2 with VEGF/ vascular endothelial growth factor receptor 2 (VEGFR2) (Flk1), in combination, induced by MSCs enhances angiogenesis and vascular integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
201
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(214 citation statements)
references
References 35 publications
13
201
0
Order By: Relevance
“…This capacity of MSCs may be of particular importance in facilitating EC migration into dense micro-organs such as islets. In addition, MSCs most likely contributed growth factors and extracellular matrix production that serve to encourage the stabilization and maturation of the EC sprouts (9). This effect of MSCs was evidenced by the increased sprout formation by EC-MSC islets in fibrin gels, where close interactions between EC sprouts and MSCs occurred to a high degree.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This capacity of MSCs may be of particular importance in facilitating EC migration into dense micro-organs such as islets. In addition, MSCs most likely contributed growth factors and extracellular matrix production that serve to encourage the stabilization and maturation of the EC sprouts (9). This effect of MSCs was evidenced by the increased sprout formation by EC-MSC islets in fibrin gels, where close interactions between EC sprouts and MSCs occurred to a high degree.…”
Section: Discussionmentioning
confidence: 97%
“…MSCs have also been shown to upregulate the expression of angiopoietin and vascular endothelial growth factor (VEGF) in ECs, contributing to an increase in angiogenesis and stabilization of the vasculature (9). Moreover, MSCs have been shown to possess important immune-modulating properties (10), and they do not trigger adaptive immune reactions, which could make them ideal in islet transplantation setting (11,12).…”
mentioning
confidence: 99%
“…Therefore, it is important in the clinical treatment of cerebral ischemia to improve or restore cerebral blood flow in early cerebral ischemia. Many evidences have shown that a higher microvessel density means a significantly better prognosis for patients with stroke, and angiogenesis can improve blood perfusion in brain tissue surrounding the ischemic area in rats and promote neurological function recovery after ischemia (Zacharek et al., 2007). Meanwhile, some studies found that cerebral ischemia can cause auto‐angiogenesis in the ischemic region (Beck & Plate, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We first referred to two classic endothelial angiogenesis-related pathways both in vitro and in vivo: VEGF signaling [6,7,22] and angiopoietin/TIE2 signaling [34,35]. However, the RNA-seq results did not show significant elevation of upstream ligands or receptors for these pathways in co-HUVECs within 24 h. Alternatively, unbiased analysis demonstrated that a large proportion of experimentally validated NF-kB target genes (mainly based on www.bu.edu/NF-kB/gene-resources/target genes) were upregulated upon coculture for 12 and 24 h in both co-HUVECs and co-HMSCs (Fig.…”
Section: Rna-seq Revealed Differential Gene Expression Profiles and Amentioning
confidence: 99%